A community-based cross-sectional study of COVID-19 and psychological distress using the impact of event scale revised among recovered patients of COVID-19 - Mushtaq, Beenish; Jan, Yasmeen; Bhat, Ashfaq Ahmad; Deeba, Farah (ScienceRise: medical science (Online), 2023)
COVID-19 infection is a potentially traumatic experience in terms of the risk of running a Severe Acute Respiratory Syndrome in addition to the social implications of the disease in terms of being isolated and follow up of strict quarantine measures of close contact. The purpose of this study was to assess the prevalence of psychological distress and its risk factors in patients who develop COVID-19 infection. There is scanty evidence regarding the magnitude of COVID-19-related psychological distress (PD) among the general population of India, and Post Traumatic Stress Disorder (PTSD) is a Mental Disorder that develops after a traumatic event that has a life-threatening impact. The aim of this study was to assess COVID-19 infection. Material and methods: This study was conducted among 672 COVID-19 survivors of district Budgam from (March to August 2020). They were contacted by telephone, and psychological distress in the post-COVID recovery period was assessed using the IES-R scale. This is a 22-item scale, and each item is rated on a scale ranging from 0-4. Suitable Statistical Analysis was done to analyze risk factors for the development of any psychological distress. Methods: Descriptive cross-sectional study. Study design: Cross-sectional study from District Budgam of Kashmir Division. Study tool: using the IES-R scale for PTSD. Result: In our study prevalence of psychological distress using IES –R was mild in (7.08 %) of the study participants and moderate in (1.06 %) of the study participants. Psychological distress in study participants was examined by age, sex, employment status, family history, COVID-19 disease status and history of hospitalization. No statistical significance between age, gender, days of hospitalization and PTSD was seen. However, statistical significance with the IES–R score was seen between family history and the presence and absence of symptoms in the study subjects. Conclusion: As the pandemic crisis seems to be ebbing, the current findings help us to identify risk factors and devise pragmatic strategies to curtail the burden of mental issues and successfully meet the challenges that follow the pandemic Інфекція COVID-19 є потенційно травматичним досвідом з точки зору ризику розвитку важкого гострого респіраторного синдрому на додаток до соціальних наслідків захворювання з точки зору ізоляції та дотримання суворих карантинних заходів з метою попередження контактів. Метою цього дослідження було оцінити поширеність психологічного дистресу та його факторів ризику у пацієнтів, у яких розвивається інфекція COVID-19. Є мізерні докази щодо масштабів психологічного дистресу (ПД), пов’язаного з COVID-19, серед населення Індії в цілому, а посттравматичний стресовий розлад (ПТСР) — це психічний розлад, який розвивається після травматичної події, що загрожує життю. Метою цього дослідження було оцінити інфікування COVID-19 та його наслідки. Матеріал і методи: це дослідження було проведено серед 672 осіб, які пережили COVID-19 з Будгамського району (з березня по серпень 2020 р.). З ними спілкувалися по телефону та оцінювали психологічний стрес у період одужання після COVID за допомогою шкали IES-R. Це шкала з 22 пунктів, і кожен пункт оцінюється за шкалою від 0 до 4. Для аналізу факторів ризику розвитку будь-якого психологічного дистресу було проведено відповідний статистичний аналіз. Методи: описове перехресне дослідження. Дизайн дослідження: перехресне дослідження в районі Будгаму, Кашмірського округу. Інструмент дослідження: використання шкали IES-R для ПТСР. Результат: у нашому дослідженні поширеність психологічного дистресу при використанні IES-R була легкою у (7,08 %) учасників дослідження та помірною у (1,06 %) учасників дослідження. Психологічний дистрес учасників дослідження вивчався за віком, статтю, статусом зайнятості, сімейним анамнезом, статусом захворювання на COVID-19 та історією госпіталізації. Не спостерігалося статистичної значущості між віком, статтю, днями госпіталізації та посттравматичним стресовим розладом, однак статистична значущість за шкалою IES–R спостерігалася між сімейною історією, та наявністю або відсутністю симптомів у суб’єктів дослідження. Висновок: оскільки пандемічна криза, схоже, йде на спад, поточні результати допомагають нам визначити фактори ризику та розробити прагматичні стратегії, щоб зменшити тягар психічних проблем і успішно протистояти викликам, пов’язаним з пандемією